2013
DOI: 10.1103/physrevb.88.134102
|View full text |Cite
|
Sign up to set email alerts
|

Point defect modeling in materials: Couplingab initioand elasticity approaches

Abstract: Modeling point defects at an atomic scale requires to take special care of the long range atomic relaxations. This elastic field can strongly affect point defect properties calculated in atomistic simulations, because of the finite size of the system under study. This is an important restriction for ab initio methods which are limited to a few hundred atoms. We propose an original approach coupling ab initio calculations and linear elasticity theory to obtain the properties of the isolated point defect for red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 42 publications
6
156
1
1
Order By: Relevance
“…Because our supercells are more than twice this distance in each direction, we think that the interaction between supercell replicas should have little effect on binding and migration energies. For isolated solutes and vacancy we used the ANETO code 38 to compute the elastic interaction energy between supercell replicas; it is less than 8%, 4% and 10% of the formation energy, respectively for C, O and N-vacancy, which is acceptable. The thickness of the UN(001) surface slab geometries was chosen following the work by Bocharov 15,16 , who showed that defect formation energies are converged for slabs thicker than five atomic layers.…”
Section: A Density-functional Theory Calculationsmentioning
confidence: 99%
“…Because our supercells are more than twice this distance in each direction, we think that the interaction between supercell replicas should have little effect on binding and migration energies. For isolated solutes and vacancy we used the ANETO code 38 to compute the elastic interaction energy between supercell replicas; it is less than 8%, 4% and 10% of the formation energy, respectively for C, O and N-vacancy, which is acceptable. The thickness of the UN(001) surface slab geometries was chosen following the work by Bocharov 15,16 , who showed that defect formation energies are converged for slabs thicker than five atomic layers.…”
Section: A Density-functional Theory Calculationsmentioning
confidence: 99%
“…The defect formation energies (Emultiplied by the bulk modulus of the perfect t-ZrO 2 structure, with the aid of the ANETO software package [40].…”
Section: Simulationsmentioning
confidence: 99%
“…In super cell calculations, point defects (here the solute atoms) are interacting with their images, and to evalu ate the effects of elastic strains the energies associated with those long-range elastic inter ac tions must be corrected. Application of a recently proposed method for this correction [34], which is expected to ameliorate the situation, is now under way.…”
Section: Theoretical Approachesmentioning
confidence: 99%